Effect of Different Reaction Parameters on the Synthesis of Biodiesel from Soybean Oil Using Acid Ionic Liquid as Catalyst - Du, Huan; Fang, Miaoli; Song, Lelian; Tan, Zhongqin; He, Yanfei; Han, Xiaoxiang (Asian Journal of Chemistry, 2014)
Response surface methodology (RSM) was successfully applied to optimize transesterification of biodiesel from soybean oil catalyzed by ionic liquid. The effects of various reaction conditions, including reaction time, methanol/oil molar ratio and the amount of ionic liquid were investigated. A central composite design (CCD) was employed to search for the optimal yield of biodiesel. The obtained optimum conditions were n(soybean oil):n(methanol) = 1:13, amount of catalyst of 4 wt. % to soybean oil and reaction time 8.5 h at 120 °C. Under the optimized conditions, the yield of biodiesel reached 94.7 %, in close agreement with values predicted by the mathematical model. The [HSO3-pmim]HSO4 ionic liquid showed the best catalytic activity, highly stability on the transesterification of soybean oil and could be reused six times without noticeable drop in activity.